Understanding media psychology - Stever, Gayle; Giles, David 1964-; Cohen, J. David 1976-; Myers, Mary E. (Routledge, is an imprint of the Taylor & Francis, 2022)
"Understanding Media Psychology is the perfect introductory textbook to the growing field of media psychology and its importance in society, summarizing key concepts and theories to provide an overview of topics in the field. Media is present in almost every area of life today, and is an area of study that will only increase in importance as the world becomes ever more interconnected. Written by a team of expert authors, this book will help readers to understand the structures, influences and theories around media psychology. Covering core areas such as positive media psychology, the effects of gaming, violence, advertising and pornography, the authors critically engage with contemporary discussions around propaganda, fake news, deep fakes, and the ways media have informed the COVID-19 pandemic. Particular care is also given to addressing the interaction between issues of social justice and the media, as well as the effects media has on both the members of marginalized groups and the way those groups are perceived. A final chapter addresses the nature of the field moving forward, and how will continue to interact with closely related areas of study. Containing a range of pedagogical features are present throughout to aid teaching and student learning, including vocabulary and key terms, discussion questions, and boxed examples, this is an essential resource for media psychology courses at undergraduate and introductory master's level globally"--Provided by publisher.